2023
DOI: 10.1021/acs.est.3c02225
|View full text |Cite
|
Sign up to set email alerts
|

Sulfate Formation by Photosensitization in Mixed Incense Burning–Sodium Chloride Particles: Effects of RH, Light Intensity, and Aerosol Aging

Abstract: Elevated particulate sulfate concentrations have been frequently observed in coastal areas when air masses are influenced by continental emissions, especially combustion sources like biomass burning. We studied the SO2 uptake by laboratory-generated droplets containing incense smoke extracts and sodium chloride (IS–NaCl) under irradiation and found enhanced sulfate production over pure NaCl droplets, attributable to photosensitization induced by constituents in IS. Low relative humidity and high light intensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 105 publications
0
8
0
Order By: Relevance
“…It is important to note that these studies have focused on the photolysis of O 3 under shortwave ultraviolet light (λ = 254 nm), which differs from tropospheric conditions. Recent studies have found the photo-oxidation of SO 2 to produce sulfate in NaCl droplets under the coexistence of NO 2 or photosensitizers , and photocatalytic chlorine atom production on mineral dust–sea spray aerosols . These results highlight the importance of the NaCl aqueous-phase photochemistry in sulfate formation.…”
Section: Introductionmentioning
confidence: 84%
“…It is important to note that these studies have focused on the photolysis of O 3 under shortwave ultraviolet light (λ = 254 nm), which differs from tropospheric conditions. Recent studies have found the photo-oxidation of SO 2 to produce sulfate in NaCl droplets under the coexistence of NO 2 or photosensitizers , and photocatalytic chlorine atom production on mineral dust–sea spray aerosols . These results highlight the importance of the NaCl aqueous-phase photochemistry in sulfate formation.…”
Section: Introductionmentioning
confidence: 84%
“…The significant sulfate formation observed in our experiments suggests that such a process can be a potential missing sulfate pathway in the atmosphere. Recently, we found a significant sulfate formation from the SO 2 uptake into the particles containing sodium chloride and extracts of incense burning particles, a proxy of biomass burning particles, under irradiation. While SO 2 was used as a precursor in the present study to investigate the interaction between chlorine chemistry and photosensitizer in oxidative capacity, further investigation is needed to determine their effect on the oxidation of organic precursor in forming secondary organic aerosol (SOA).…”
Section: Atmospheric Implicationmentioning
confidence: 99%
“…Further, this study focused on certain aromatic carbonyls, but there are other less-studied organic photosensitizers with greater 3 C* formation efficiency (e.g., benzophenone and xanthone) . Future studies should also explore more multicomponent mixtures involving other organic compounds (e.g., aliphatic polyols and carboxylic acids) and inorganic compounds (e.g., ammonium nitrate, ,, ammonium chloride, and sulfur dioxide ,, ), especially those with high atmospheric abundance, for a better understanding of atmospheric photosensitization.…”
Section: Atmospheric Implicationsmentioning
confidence: 99%
“…Aqueous-phase photoreactions of aromatic carbonyl photosensitizers and phenols contribute to the aqueous secondary organic aerosol (aqSOA) and brown carbon (BrC) budget. BrC are organic aerosols that strongly absorb near-ultraviolet (UV) and visible light . Aromatic carbonyls and phenols are emitted by biomass burning (BB), photolysis of polycyclic aromatic hydrocarbons (PAHs), photochemical oxidation of aromatic compounds, automotive emissions, and laboratory-generated incense smoke . Several studies have explored the reactions of phenolic compounds mediated by various reactive species, including hydroxyl radicals ( • OH), singlet oxygen ( 1 O 2 ), ozone (O 3 ), , reactive nitrogen species (e.g., • NO and • NO 2 ), , and triplet excited state of organic compounds ( 3 C*). , , In particular, there has been a growing recognition of the importance of photosensitized phenol oxidation by 3 C*, such as those from aromatic carbonyls. , , For example, relative to • OH oxidation, 3 C*-driven phenol oxidation has been reported to produce higher aqSOA mass yields at faster rates due to greater oxidant concentration in 3 C*-initiated reaction.…”
Section: Introductionmentioning
confidence: 99%